Pengaruh Senam Aerobic Low Impact terhadap Peningkatan V02max - Helvi Darsi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
This study aims to see the effect of low impact aerobic exercise on VO2Max capacity improvement. The population in this study were students of SMK Negeri 1 Curup who follow extracurricular aerobic exercise. Sampling was done by purposive randome sampling technique which amounted to 24 people. The analysis was done by measuring the ability of VO2Max through bleep test test before and after given low impact aerobic exercise. Data were analyzed by different test formula t test. The result of the research is thitung 6.04 greater than t table 1.714 H0 is rejected and Ha is accepted meaning hypothesis stating there is significant influence between low impact Aerobic aerobic exercise to increase VO2max student SMK Negeri 1 Curup accepted empirically truth. The result of research that there is significant influence by low impact aerobic gymnastics exercise to increase VO2Max Student SMK Negeri 1 Curup who follow extracurricularaerobicgymnastics. Keywords: Aerobic Low Impact, VO2Max